Microbiological Analysis of Liquid Lipstick Products Used by Makeup Artists - Chairunnisaa Jabal Rahmah; Sri Pujiyanto; Isworo Rukmi (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2021)
AbstractLipstick is a non-sterile pharmaceutical product that is used for make-up on the lips. Liquid lipstick used by makeup artists may have a high level of microbial contamination because they are applied to different clients in turn. This study aims to determine the microbiological quality of liquid lipstick used by makeup artists based on the result of the Bacterial Total Plate Count (TPC), Yeast and Mold Count (YMC), and the presence of pathogenic microbes. Three samples of liquid lipstick were taken from three different makeup artists and one sample was a new liquid lipstick product. The Bacterial TPC test was carried out on TSA media and the YMC test was carried out on SDA with the spread plate technique. The presence of microbial pathogens P. aeruginosa, S. aureus, and C. albicans were carried out on selective media. The results of bacterial TPC was 9.0 × 103 to 3.0 × 104 CFU/mL, while the YMC was 1.1 × 103 to 3.1 × 103 CFU/mL. The pathogenic microbes detected were S. aureus in 2 samples and C. albicans in 1 sample. The bacterial TPC and YMC values exceed the contamination limit based on BPOM Regulation No. 12/2019.